Integrated Teacher Support Systems for Enhancing Behavioral and Cognitive Development in Preschool Institutions - Lucky Dewanti (Asian Journal of Applied Education (AJAE), 2026)
The quality of early childhood behavioral and cognitive development is strongly influenced by teacher capacity and institutional support, yet teacher support practices are often fragmented. This mixed-methods sequential explanatory study examines the impact of an integrated teacher support system on children’s behavioral and cognitive development in early childhood education institutions. Quantitative data were collected from 50 teachers across nine institutions in Bogor Regency and assessments of 120 children, and analyzed using descriptive and inferential statistics. Qualitative data were obtained through in-depth interviews with six teachers and institutional leaders and analyzed thematically. The findings indicate that an integrated teacher support system positively enhances children’s behavioral and cognitive development by strengthening teachers’ pedagogical competence, ensuring consistency in learning practices, and providing sustained institutional support. The study contributes to early childhood education theory and offers practical guidance for designing integrated and sustainable teacher support systems.